Role of glycerides of organic acids on broiler recovery challenged with the Newcastle disease virus (NDV) isolated from broiler chicken fields - Merkhan M. Mustafa; Renas H. Isa; Saifaddin A.A. Zangana; Hassan, Warzan H. (Zanco Journal of Pure and Applied Sciences, 2024)
Newcastle disease virus is a highly contagious viral disease in poultry fields. Besides biosecurity and vaccinations, continuous outbreaks occur due to mutations in genomic sequence, resulting in new vaccine strains. This research hypothesized that using a mixture of short- and medium-chain fatty acids may protect the broiler chickens from this disease and improve the broiler performance. A sample from the NDV-like outbreak was collected from broiler chickens having high mortality and several lesion symptoms in the tracheae, lung, and gastrointestinal tract. Two hundred four broiler chicks were randomly divided into four treatments, including three replicates each. T1 negative control with no additives; T2 control in which the chicks received 2 ml/L of glycerides of organic acids; T3 2 ml/L of glycerides of organic acids + infected with NDV isolate; T4 infected with the NDV isolate. The results showed that the sample was NDV positive by Reverse Transcriptase Real-Time PCR. All the studied performance parameters were significantly improved in the group that had glycerides of organic acids with no infection. However, these compounds could not protect and minimize the mortality of chickens infected with a Newcastle disease virus field isolate. This study concludes that this mixture improves broiler performance in normal conditions.